Anti-static rubber floor mat and production process thereof

By designing a structure including base layer and soft layer in the rubber pad, the impact resistance and anti-static properties of the rubber pad are improved by using specific materials, the problems of poor impact resistance and electrostatic resistance of existing rubber pads are solved, extending the service life and improving the Anti-static effect.

CN119261323APending Publication Date: 2025-01-07XUANCHENG NEW RUNFA POLYMER TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411256554.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing rubber pads have shortcomings in impact resistance and electrostatic problems, and have poor impact resistance and are prone to static electricity, which affects the service life.

Method used

Designed with rubber floor mats including base layer and soft layer, the base layer consists of rubber material, modified talc powder, butyl acetate, bisphenol F-type liquid epoxy resin, conductive materials, antioxidants, modified sulfur and modified graphite , enhance the soft layer through foaming agent, improve impact absorption and vertical deformation capabilities, and prevent static accumulation.

Benefits of technology

It significantly improves the impact resistance and anti-static properties of rubber pads, extends the service life, and effectively prevents static accumulation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119261323A_ABST
    Figure CN119261323A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of ground mats, particularly relates to an anti-static rubber ground mat and a production process thereof, and provides the following scheme aiming at the problems that an existing anti-static rubber ground mat is small in impact absorption and vertical deformation capacity and prone to gathering static electricity. The anti-static rubber ground mat comprises a base layer, a soft layer adhered to the top of the base layer and ground mat cloth adhered to the top of the soft layer, wherein the base layer is prepared from the following raw materials in parts by weight: 45 to 65 parts of rubber material, 6 to 10 parts of modified talcum powder, 1 to 5 parts of butyl acetate, 7 to 10 parts of bisphenol F type liquid epoxy resin, 10 to 15 parts of conductive material, 1 to 3 parts of antioxidant and 8 parts of anti-oxidant; the foaming agent is added into 12 parts of modified sulfur and 6-10 parts of modified graphite, the soft layer can be manufactured, the soft layer and the base layer can be connected together, the impact resistance of the rubber pad can be enhanced, the impact absorption capacity and the vertical deformation capacity are both improved, and static electricity accumulation is prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of floor mats, and in particular to an antistatic rubber floor mat and a production process thereof. Background Art

[0002] A Chinese patent document with application number 202011098101.9 discloses a method for making a rubber pad and a rubber pad, comprising the following steps: prefabricating a first plate and a second plate, treating the surface of the first plate with sodium naphthalene, and opening a plurality of through holes on the second plate; prefabricating a plurality of films having a size smaller than the mold cavity; placing the first plate in the mold cavity, superimposing a layer of film on the first plate, superimposing the second plate on the film, and continuing to superimpose a layer of film on the second plate, coating the sides of the first plate and the second plate with a layer of glue, and injecting glue into the mold cavity so that the glue fills the gap between the film and the mold cavity; closing the mold for vulcanization, and the rubber pad is manufactured using any of the above-mentioned methods for making a rubber pad. The processed rubber pad has uniform thickness, complete rubber coating, is not easy to rust, and has a longer service life. The present invention is used in the field of rubber pads.

[0003] However, there are some problems with the manufacturing method of the rubber pad and the rubber pad, for example, the impact resistance is poor, the impact absorption capacity is poor, the vertical deformation is small, which affects the impact resistance of the rubber pad, and the rubber pad is prone to generate a large amount of static electricity, which affects the use of the rubber pad. Summary of the invention

[0004] Based on the problem that the background technology has low impact absorption and vertical deformation capabilities and is prone to static electricity accumulation, the present invention proposes an anti-static rubber floor mat and a production process thereof.

[0005] The present invention provides an antistatic rubber floor mat, which comprises a base layer, a soft layer bonded to the top of the base layer, and a floor mat cloth bonded to the top of the soft layer: The raw material composition and weight proportion of the base layer include 45 to 65 parts of rubber material, 6 to 10 parts of modified talc powder, 1 to 5 parts of butyl acetate, 7 to 10 parts of bisphenol F type liquid epoxy resin, 10 to 15 parts of conductive material, 1 to 3 parts of antioxidant, 8 to 12 parts of modified sulfur and 6 to 10 parts of modified graphite; The raw material composition and weight proportion of the soft layer include 98 parts of base rubber mix and 2 parts of foaming agent; The rubber material includes one or two of natural rubber, nitrile rubber, butadiene rubber and polyisoprene rubber; the conductive material includes carbon fiber, stainless steel fiber and metal powder; the base material is manufactured by rubber material, modified talcum powder, butyl acetate, bisphenol F liquid epoxy resin, conductive material, antioxidant, modified sulfur and modified graphite, and then a foaming agent is added to produce a soft layer; the soft layer and the base layer can be connected together to enhance the impact resistance of the rubber pad, and the impact absorption and vertical deformation capabilities are improved to prevent static electricity accumulation.

[0006] Preferably, the raw materials for preparing the modified talc powder include talc powder, boron nitride, ethylhexyl phosphoric acid, organic ammonium salt and ethanol, and the weight ratio of talc powder, boron nitride, ethylhexyl phosphoric acid, organic ammonium salt and ethanol in the modified talc powder is 11:3:1:1:13.

[0007] Preferably, the preparation method of the modified talc comprises: obtaining talc, boron nitride, ethylhexyl phosphoric acid, an organic ammonium salt and ethanol in proportion, adding talc to ethanol, mixing and stirring using a high-speed stirrer to make a slurry, then adding boron nitride, ethylhexyl phosphoric acid and an organic ammonium salt to the slurry, mixing and stirring again, heating the temperature to 60°C during the mixing process, mixing for 15 minutes, using a pelletizing machine to make granular pills, putting the granular pills into a carbonization furnace, introducing argon gas for protection, starting the carbonization furnace for heating and carbonization, the granular pills gradually graphitize at high temperature, discharging after cooling to room temperature, and finally crushing and screening to obtain modified talc, which can enhance the compatibility of talc.

[0008] Preferably, the weight proportions of carbon fiber, stainless steel fiber and metal powder in the conductive material are 2:2:5, the length of the carbon fiber is 1mm to 2mm, the length of the stainless steel fiber is 1mm to 5mm, the metal powder is one of iron powder, aluminum powder and copper powder, and the particle size of the metal powder is 0.01mm to 0.10mm.

[0009] Preferably, the materials for preparing the modified sulfur include sulfur, shell powder, acrylic resin, silane coupling agent and water, and the weight ratio of sulfur, shell powder, acrylic resin, silane coupling agent and water in the modified sulfur is 5:2:3:1:20.

[0010] Preferably, the preparation method of the modified sulfur is: pouring shell powder into water and mixing to prepare a powder suspension, adding a silane coupling agent to the powder suspension, and pouring it into a grinding device for grinding to a particle size of 5μm to 50μm, then adding acrylic resin and stirring for 60 minutes to 120 minutes, then adding sulfur and accelerating stirring for 1 hour to obtain a sulfur mixture, and finally drying and dehydrating it, crushing and sieving it to obtain modified sulfur.

[0011] Preferably, the preparation method of the modified graphite is as follows: graphite, potassium permanganate, citric acid and ethanol are prepared, the graphite is crushed and graded to obtain a shaped graphite material, the graphite, potassium permanganate and ethanol are evenly mixed, and then placed in a vacuum pump for vacuum impregnation, filtered and dried, poured into deionized water for mixing, and hydrothermally reacted at a temperature of 160°C to 200°C, and then a solid precursor is obtained by solid-liquid separation, and citric acid is added for mixing and stirring, and the mixture is placed in a vacuum pump for vacuum impregnation again. After filtering and drying, the mixture is buried at a high temperature to obtain modified graphite.

[0012] A production process for an antistatic rubber floor mat comprises the following steps: S1: Weigh rubber material, modified talcum powder, butyl acetate and bisphenol F liquid epoxy resin according to proportion, pour them into a rubber kneading machine, knead and pound the rubber, take out the material after 10 minutes of operation to obtain a mixed rubber, add the mixed rubber to an open mill for plastication to obtain a masterbatch; S2: The masterbatch is transferred into an internal mixer, and then antioxidant and modified graphite are added into the internal mixer, and mixed under high temperature and high shear conditions. The mixing time is controlled within 3 minutes, and then conductive material and modified sulfur are added, and conventional internal mixing is performed to obtain a base compound rubber; S3: Take one third of the base layer rubber mix, add a foaming agent and continue mixing to obtain a soft layer rubber mix; S4: pour the base layer rubber mixture into the bottom of the mold, then spread the soft layer rubber mixture on the base layer rubber mixture, press mold to form, and take out the semi-finished floor mat; S5: The floor mat is glued to the semi-finished product by gluing to obtain an anti-static rubber floor mat.

[0013] Preferably, in S2, the speed of the internal mixer is controlled at 150 r / min to 170 r / min, and the temperature of the cooling water is controlled at 40° C. to 50° C.

[0014] Preferably, in S4, compression molding is performed under a pressure condition of 10 MPa to 12 MPa, and the compression molding time is 20 minutes.

[0015] Beneficial effects of the present invention: The base material is made of rubber, modified talcum powder, butyl acetate, bisphenol F liquid epoxy resin, conductive material, antioxidant, modified sulfur and modified graphite, and then a foaming agent is added to produce a soft layer. The soft layer and the base layer can be connected together to enhance the impact resistance of the rubber pad, improve the impact absorption and vertical deformation capabilities, and prevent static electricity accumulation. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The working flow chart proposed by the present invention. DETAILED DESCRIPTION

[0017] The present invention will be further explained below in conjunction with specific embodiments.

[0018] Reference Figure 1 , Embodiment 1 This embodiment provides an antistatic rubber floor mat, which includes a base layer, a soft layer bonded to the top of the base layer, and a floor mat cloth bonded to the top of the soft layer: The raw material composition of the base layer and its weight parts include 52 parts of rubber material, 8 parts of modified talc, 1 part of butyl acetate, 8 parts of bisphenol F type liquid epoxy resin, 12 parts of conductive material, 2 parts of antioxidant, 10 parts of modified sulfur and 7 parts of modified graphite; The raw material composition and weight proportion of the soft layer include 98 parts of base rubber mix and 2 parts of foaming agent; The rubber material includes natural rubber and polyisoprene rubber, and the conductive material includes carbon fiber, stainless steel fiber and metal powder; The raw materials for preparing the modified talc powder include talc powder, boron nitride, ethylhexyl phosphoric acid, organic ammonium salt and ethanol, and the weight ratio of talc powder, boron nitride, ethylhexyl phosphoric acid, organic ammonium salt and ethanol in the modified talc powder is 11:3:1:1:13; The preparation method of modified talcum powder comprises the following steps: obtaining talcum powder, boron nitride, ethylhexyl phosphoric acid, organic ammonium salt and ethanol in proportion, adding talcum powder to ethanol, mixing and stirring with a high-speed stirrer to prepare a slurry, then adding boron nitride, ethylhexyl phosphoric acid and organic ammonium salt to the slurry, mixing and stirring again, heating the temperature to 60° C. during the mixing process, mixing for 15 minutes and preparing granular pills with a pill making machine, placing the granular pills in a carbonization furnace, introducing argon gas for protection, starting the carbonization furnace for heating and carbonization, and gradually graphitizing the granular pills at high temperature, discharging the materials after cooling to room temperature, and finally crushing and screening to prepare modified talcum powder; The weight proportions of carbon fiber, stainless steel fiber and metal powder in the conductive material are 2:2:5, the length of the carbon fiber is 1 mm, the length of the stainless steel fiber is 2 mm, the metal powder is one of iron powder, aluminum powder and copper powder, and the particle size of the metal powder is 0.05 mm; The materials for preparing the modified sulfur include sulfur, shell powder, acrylic resin, silane coupling agent and water, and the weight ratio of sulfur, shell powder, acrylic resin, silane coupling agent and water in the modified sulfur is 5:2:3:1:20; Preparation method of modified sulfur: pour shell powder into water and mix to prepare powder suspension, add silane coupling agent into the powder suspension, pour into grinding equipment for grinding, grind to a particle size of 20 μm, then add acrylic resin and stir for 80 minutes, then add sulfur and accelerate stirring for 1 hour to obtain a sulfur mixture, finally dry and dehydrate, crush and sieve to obtain modified sulfur; Preparation method of modified graphite: prepare graphite, potassium permanganate, citric acid and ethanol, crush and grade the graphite to obtain shaped graphite material, mix the graphite, potassium permanganate and ethanol evenly, put them into a vacuum pump for vacuum impregnation, filter and dry, pour deionized water into them for mixing, carry out hydrothermal reaction at a temperature of 180°C, obtain a solid precursor through solid-liquid separation, add citric acid for mixing and stirring, put them into a vacuum pump for vacuum impregnation again, filter and dry, bury the mixture at carbon high temperature to obtain modified graphite; The base material is made of rubber, modified talcum powder, butyl acetate, bisphenol F liquid epoxy resin, conductive material, antioxidant, modified sulfur and modified graphite, and then a foaming agent is added to produce a soft layer. The soft layer and the base layer can be connected together to enhance the impact resistance of the rubber pad, improve the impact absorption and vertical deformation capabilities, and prevent static electricity accumulation.

[0019] A production process for an antistatic rubber floor mat comprises the following steps: S1: Weigh rubber material, modified talcum powder, butyl acetate and bisphenol F liquid epoxy resin according to proportion, pour them into a rubber kneading machine, knead and pound the rubber, take out the material after 10 minutes of operation to obtain a mixed rubber, add the mixed rubber to an open mill for plastication to obtain a masterbatch; S2: The masterbatch is transferred into an internal mixer, and then antioxidant and modified graphite are added into the internal mixer, and mixed under high temperature and high shear conditions. The speed of the internal mixer is controlled at 160r / min, the cooling water temperature is controlled at 45°C, and the mixing time is controlled at 3 minutes. Then, the conductive material and modified sulfur are added, and conventional internal mixing is performed to obtain a base compound rubber; S3: Take one third of the base layer rubber mix, add a foaming agent and continue mixing to obtain a soft layer rubber mix; S4: pouring the base rubber mixture into the bottom of the mold, and then spreading the soft layer rubber mixture on the base rubber mixture, and performing compression molding at a pressure of 11 MPa for 20 minutes, and taking out the semi-finished floor mat; S5: The floor mat is glued to the semi-finished product by gluing to obtain an anti-static rubber floor mat.

[0020] Reference Figure 1 , Embodiment 2 This embodiment provides an antistatic rubber floor mat, which includes a base layer, a soft layer bonded to the top of the base layer, and a floor mat cloth bonded to the top of the soft layer: The raw material composition of the base layer and its weight parts include 48 parts of rubber material, 6 parts of modified talc, 2 parts of butyl acetate, 8 parts of bisphenol F type liquid epoxy resin, 14 parts of conductive material, 2 parts of antioxidant, 11 parts of modified sulfur and 9 parts of modified graphite; The raw material composition and weight proportion of the soft layer include 98 parts of base rubber mix and 2 parts of foaming agent; The rubber material includes natural rubber and polyisoprene rubber, and the conductive material includes carbon fiber, stainless steel fiber and metal powder; The raw materials for preparing the modified talc powder include talc powder, boron nitride, ethylhexyl phosphoric acid, organic ammonium salt and ethanol, and the weight ratio of talc powder, boron nitride, ethylhexyl phosphoric acid, organic ammonium salt and ethanol in the modified talc powder is 11:3:1:1:13; The preparation method of modified talcum powder comprises the following steps: obtaining talcum powder, boron nitride, ethylhexyl phosphoric acid, organic ammonium salt and ethanol in proportion, adding talcum powder to ethanol, mixing and stirring with a high-speed stirrer to prepare a slurry, then adding boron nitride, ethylhexyl phosphoric acid and organic ammonium salt to the slurry, mixing and stirring again, heating the temperature to 60° C. during the mixing process, mixing for 15 minutes and preparing granular pills with a pill making machine, placing the granular pills in a carbonization furnace, introducing argon gas for protection, starting the carbonization furnace for heating and carbonization, and gradually graphitizing the granular pills at high temperature, discharging the materials after cooling to room temperature, and finally crushing and screening to prepare modified talcum powder; The weight proportions of carbon fiber, stainless steel fiber and metal powder in the conductive material are 2:2:5, the length of the carbon fiber is 1 mm, the length of the stainless steel fiber is 2 mm, the metal powder is one of iron powder, aluminum powder and copper powder, and the particle size of the metal powder is 0.05 mm; The materials for preparing the modified sulfur include sulfur, shell powder, acrylic resin, silane coupling agent and water, and the weight ratio of sulfur, shell powder, acrylic resin, silane coupling agent and water in the modified sulfur is 5:2:3:1:20; Preparation method of modified sulfur: pour shell powder into water and mix to prepare powder suspension, add silane coupling agent into the powder suspension, pour into grinding equipment for grinding, grind to a particle size of 20 μm, then add acrylic resin and stir for 80 minutes, then add sulfur and accelerate stirring for 1 hour to obtain a sulfur mixture, finally dry and dehydrate, crush and sieve to obtain modified sulfur; Preparation method of modified graphite: prepare graphite, potassium permanganate, citric acid and ethanol, crush and grade the graphite to obtain shaped graphite material, mix the graphite, potassium permanganate and ethanol evenly, put them into a vacuum pump for vacuum impregnation, filter and dry, pour deionized water into them for mixing, carry out hydrothermal reaction at a temperature of 180°C, obtain a solid precursor through solid-liquid separation, add citric acid for mixing and stirring, put them into a vacuum pump for vacuum impregnation again, filter and dry, bury the mixture at carbon high temperature to obtain modified graphite; The base material is made of rubber, modified talcum powder, butyl acetate, bisphenol F liquid epoxy resin, conductive material, antioxidant, modified sulfur and modified graphite, and then a foaming agent is added to produce a soft layer. The soft layer and the base layer can be connected together to enhance the impact resistance of the rubber pad, improve the impact absorption and vertical deformation capabilities, and prevent static electricity accumulation.

[0021] A production process for an antistatic rubber floor mat comprises the following steps: S1: Weigh rubber material, modified talcum powder, butyl acetate and bisphenol F liquid epoxy resin according to proportion, pour them into a rubber kneading machine, knead and pound the rubber, take out the material after 10 minutes of operation to obtain a mixed rubber, add the mixed rubber to an open mill for plastication to obtain a masterbatch; S2: The masterbatch is transferred into an internal mixer, and then antioxidant and modified graphite are added into the internal mixer, and mixed under high temperature and high shear conditions. The speed of the internal mixer is controlled at 160r / min, the cooling water temperature is controlled at 45°C, and the mixing time is controlled at 3 minutes. Then, the conductive material and modified sulfur are added, and conventional internal mixing is performed to obtain a base compound rubber; S3: Take one third of the base layer rubber mix, add a foaming agent and continue mixing to obtain a soft layer rubber mix; S4: pouring the base rubber mixture into the bottom of the mold, and then spreading the soft layer rubber mixture on the base rubber mixture, and performing compression molding at a pressure of 11 MPa for 20 minutes, and taking out the semi-finished floor mat; S5: The floor mat is glued to the semi-finished product by gluing to obtain an anti-static rubber floor mat.

[0022] Reference Figure 1 , Embodiment 3 This embodiment provides an antistatic rubber floor mat, which includes a base layer, a soft layer bonded to the top of the base layer, and a floor mat cloth bonded to the top of the soft layer: The raw material composition of the base layer and its weight parts include 52 parts of rubber material, 6 parts of modified talc, 2 parts of butyl acetate, 7 parts of bisphenol F type liquid epoxy resin, 13 parts of conductive material, 2 parts of antioxidant, 10 parts of modified sulfur and 8 parts of modified graphite; The raw material composition and weight proportion of the soft layer include 98 parts of base rubber mix and 2 parts of foaming agent; The rubber material includes natural rubber and polyisoprene rubber, and the conductive material includes carbon fiber, stainless steel fiber and metal powder; The raw materials for preparing the modified talc powder include talc powder, boron nitride, ethylhexyl phosphoric acid, organic ammonium salt and ethanol, and the weight ratio of talc powder, boron nitride, ethylhexyl phosphoric acid, organic ammonium salt and ethanol in the modified talc powder is 11:3:1:1:13; The preparation method of modified talcum powder comprises the following steps: obtaining talcum powder, boron nitride, ethylhexyl phosphoric acid, organic ammonium salt and ethanol in proportion, adding talcum powder to ethanol, mixing and stirring with a high-speed stirrer to prepare a slurry, then adding boron nitride, ethylhexyl phosphoric acid and organic ammonium salt to the slurry, mixing and stirring again, heating the temperature to 60° C. during the mixing process, mixing for 15 minutes and preparing granular pills with a pill making machine, placing the granular pills in a carbonization furnace, introducing argon gas for protection, starting the carbonization furnace for heating and carbonization, and gradually graphitizing the granular pills at high temperature, discharging the materials after cooling to room temperature, and finally crushing and screening to prepare modified talcum powder; The weight proportions of carbon fiber, stainless steel fiber and metal powder in the conductive material are 2:2:5, the length of the carbon fiber is 1 mm, the length of the stainless steel fiber is 2 mm, the metal powder is one of iron powder, aluminum powder and copper powder, and the particle size of the metal powder is 0.05 mm; The materials for preparing the modified sulfur include sulfur, shell powder, acrylic resin, silane coupling agent and water, and the weight ratio of sulfur, shell powder, acrylic resin, silane coupling agent and water in the modified sulfur is 5:2:3:1:20; Preparation method of modified sulfur: pour shell powder into water and mix to prepare powder suspension, add silane coupling agent into the powder suspension, pour into grinding equipment for grinding, grind to a particle size of 20 μm, then add acrylic resin and stir for 80 minutes, then add sulfur and accelerate stirring for 1 hour to obtain a sulfur mixture, finally dry and dehydrate, crush and sieve to obtain modified sulfur; Preparation method of modified graphite: prepare graphite, potassium permanganate, citric acid and ethanol, crush and grade the graphite to obtain shaped graphite material, mix the graphite, potassium permanganate and ethanol evenly, put them into a vacuum pump for vacuum impregnation, filter and dry, pour deionized water into them for mixing, carry out hydrothermal reaction at a temperature of 180°C, obtain a solid precursor through solid-liquid separation, add citric acid for mixing and stirring, put them into a vacuum pump for vacuum impregnation again, filter and dry, bury the mixture at carbon high temperature to obtain modified graphite; The base material is made of rubber, modified talcum powder, butyl acetate, bisphenol F liquid epoxy resin, conductive material, antioxidant, modified sulfur and modified graphite, and then a foaming agent is added to produce a soft layer. The soft layer and the base layer can be connected together to enhance the impact resistance of the rubber pad, improve the impact absorption and vertical deformation capabilities, and prevent static electricity accumulation.

[0023] A production process for an antistatic rubber floor mat comprises the following steps: S1: Weigh rubber material, modified talcum powder, butyl acetate and bisphenol F liquid epoxy resin according to proportion, pour them into a rubber kneading machine, knead and pound the rubber, take out the material after 10 minutes of operation to obtain a mixed rubber, add the mixed rubber to an open mill for plastication to obtain a masterbatch; S2: The masterbatch is transferred into an internal mixer, and then antioxidant and modified graphite are added into the internal mixer, and mixed under high temperature and high shear conditions. The speed of the internal mixer is controlled at 160r / min, the cooling water temperature is controlled at 45°C, and the mixing time is controlled at 3 minutes. Then, the conductive material and modified sulfur are added, and conventional internal mixing is performed to obtain a base compound rubber; S3: Take one third of the base layer rubber mix, add a foaming agent and continue mixing to obtain a soft layer rubber mix; S4: pouring the base rubber mixture into the bottom of the mold, and then spreading the soft layer rubber mixture on the base rubber mixture, and performing compression molding at a pressure of 11 MPa for 20 minutes, and taking out the semi-finished floor mat; S5: The floor mat is glued to the semi-finished product by gluing to obtain an anti-static rubber floor mat.

[0024] Reference Figure 1 , Embodiment 4 This embodiment provides an antistatic rubber floor mat, which includes a base layer, a soft layer bonded to the top of the base layer, and a floor mat cloth bonded to the top of the soft layer: The raw material composition of the base layer and its weight parts include 49 parts of rubber material, 7 parts of modified talc, 2 parts of butyl acetate, 8 parts of bisphenol F type liquid epoxy resin, 14 parts of conductive material, 3 parts of antioxidant, 9 parts of modified sulfur and 8 parts of modified graphite; The raw material composition and weight proportion of the soft layer include 98 parts of base rubber mix and 2 parts of foaming agent; The rubber material includes natural rubber and polyisoprene rubber, and the conductive material includes carbon fiber, stainless steel fiber and metal powder; The raw materials for preparing the modified talc powder include talc powder, boron nitride, ethylhexyl phosphoric acid, organic ammonium salt and ethanol, and the weight ratio of talc powder, boron nitride, ethylhexyl phosphoric acid, organic ammonium salt and ethanol in the modified talc powder is 11:3:1:1:13; The preparation method of modified talcum powder comprises the following steps: obtaining talcum powder, boron nitride, ethylhexyl phosphoric acid, organic ammonium salt and ethanol in proportion, adding talcum powder to ethanol, mixing and stirring with a high-speed stirrer to prepare a slurry, then adding boron nitride, ethylhexyl phosphoric acid and organic ammonium salt to the slurry, mixing and stirring again, heating the temperature to 60° C. during the mixing process, mixing for 15 minutes and preparing granular pills with a pill making machine, placing the granular pills in a carbonization furnace, introducing argon gas for protection, starting the carbonization furnace for heating and carbonization, and gradually graphitizing the granular pills at high temperature, discharging the materials after cooling to room temperature, and finally crushing and screening to prepare modified talcum powder; The weight proportions of carbon fiber, stainless steel fiber and metal powder in the conductive material are 2:2:5, the length of the carbon fiber is 1 mm, the length of the stainless steel fiber is 2 mm, the metal powder is one of iron powder, aluminum powder and copper powder, and the particle size of the metal powder is 0.05 mm; The materials for preparing the modified sulfur include sulfur, shell powder, acrylic resin, silane coupling agent and water, and the weight ratio of sulfur, shell powder, acrylic resin, silane coupling agent and water in the modified sulfur is 5:2:3:1:20; Preparation method of modified sulfur: pour shell powder into water and mix to prepare powder suspension, add silane coupling agent into the powder suspension, pour into grinding equipment for grinding, grind to a particle size of 20 μm, then add acrylic resin and stir for 80 minutes, then add sulfur and accelerate stirring for 1 hour to obtain a sulfur mixture, finally dry and dehydrate, crush and sieve to obtain modified sulfur; Preparation method of modified graphite: prepare graphite, potassium permanganate, citric acid and ethanol, crush and grade the graphite to obtain shaped graphite material, mix the graphite, potassium permanganate and ethanol evenly, put them into a vacuum pump for vacuum impregnation, filter and dry, pour deionized water into them for mixing, carry out hydrothermal reaction at a temperature of 180°C, obtain a solid precursor through solid-liquid separation, add citric acid for mixing and stirring, put them into a vacuum pump for vacuum impregnation again, filter and dry, bury the mixture at carbon high temperature to obtain modified graphite; The base material is made of rubber, modified talcum powder, butyl acetate, bisphenol F liquid epoxy resin, conductive material, antioxidant, modified sulfur and modified graphite, and then a foaming agent is added to produce a soft layer. The soft layer and the base layer can be connected together to enhance the impact resistance of the rubber pad, improve the impact absorption and vertical deformation capabilities, and prevent static electricity accumulation.

[0025] A production process for an antistatic rubber floor mat comprises the following steps: S1: Weigh rubber material, modified talcum powder, butyl acetate and bisphenol F liquid epoxy resin according to proportion, pour them into a rubber kneading machine, knead and pound the rubber, take out the material after 10 minutes of operation to obtain a mixed rubber, add the mixed rubber to an open mill for plastication to obtain a masterbatch; S2: The masterbatch is transferred into an internal mixer, and then antioxidant and modified graphite are added into the internal mixer, and mixed under high temperature and high shear conditions. The speed of the internal mixer is controlled at 160r / min, the cooling water temperature is controlled at 45°C, and the mixing time is controlled at 3 minutes. Then, the conductive material and modified sulfur are added, and conventional internal mixing is performed to obtain a base compound rubber; S3: Take one third of the base layer rubber mix, add a foaming agent and continue mixing to obtain a soft layer rubber mix; S4: pouring the base rubber mixture into the bottom of the mold, and then spreading the soft layer rubber mixture on the base rubber mixture, and performing compression molding at a pressure of 11 MPa for 20 minutes, and taking out the semi-finished floor mat; S5: The floor mat is glued to the semi-finished product by gluing to obtain an anti-static rubber floor mat.

[0026] Reference Figure 1 Embodiment 5 This embodiment provides an antistatic rubber floor mat, which includes a base layer, a soft layer bonded to the top of the base layer, and a floor mat cloth bonded to the top of the soft layer: The raw material composition of the base layer and its weight parts include 50 parts of rubber material, 9 parts of modified talc powder, 4 parts of butyl acetate, 7 parts of bisphenol F type liquid epoxy resin, 13 parts of conductive material, 2 parts of antioxidant, 8 parts of modified sulfur and 7 parts of modified graphite; The raw material composition and weight proportion of the soft layer include 98 parts of base rubber mix and 2 parts of foaming agent; The rubber material includes natural rubber and polyisoprene rubber, and the conductive material includes carbon fiber, stainless steel fiber and metal powder; The raw materials for preparing the modified talc powder include talc powder, boron nitride, ethylhexyl phosphoric acid, organic ammonium salt and ethanol, and the weight ratio of talc powder, boron nitride, ethylhexyl phosphoric acid, organic ammonium salt and ethanol in the modified talc powder is 11:3:1:1:13; The preparation method of modified talcum powder comprises the following steps: obtaining talcum powder, boron nitride, ethylhexyl phosphoric acid, organic ammonium salt and ethanol in proportion, adding talcum powder to ethanol, mixing and stirring with a high-speed stirrer to prepare a slurry, then adding boron nitride, ethylhexyl phosphoric acid and organic ammonium salt to the slurry, mixing and stirring again, heating the temperature to 60° C. during the mixing process, mixing for 15 minutes and preparing granular pills with a pill making machine, placing the granular pills in a carbonization furnace, introducing argon gas for protection, starting the carbonization furnace for heating and carbonization, and gradually graphitizing the granular pills at high temperature, discharging the materials after cooling to room temperature, and finally crushing and screening to prepare modified talcum powder; The weight proportions of carbon fiber, stainless steel fiber and metal powder in the conductive material are 2:2:5, the length of the carbon fiber is 1 mm, the length of the stainless steel fiber is 2 mm, the metal powder is one of iron powder, aluminum powder and copper powder, and the particle size of the metal powder is 0.05 mm; The materials for preparing the modified sulfur include sulfur, shell powder, acrylic resin, silane coupling agent and water, and the weight ratio of sulfur, shell powder, acrylic resin, silane coupling agent and water in the modified sulfur is 5:2:3:1:20; Preparation method of modified sulfur: pour shell powder into water and mix to prepare powder suspension, add silane coupling agent into the powder suspension, pour into grinding equipment for grinding, grind to a particle size of 20 μm, then add acrylic resin and stir for 80 minutes, then add sulfur and accelerate stirring for 1 hour to obtain a sulfur mixture, finally dry and dehydrate, crush and sieve to obtain modified sulfur; Preparation method of modified graphite: prepare graphite, potassium permanganate, citric acid and ethanol, crush and grade the graphite to obtain shaped graphite material, mix the graphite, potassium permanganate and ethanol evenly, put them into a vacuum pump for vacuum impregnation, filter and dry, pour deionized water into them for mixing, carry out hydrothermal reaction at a temperature of 180°C, obtain a solid precursor through solid-liquid separation, add citric acid for mixing and stirring, put them into a vacuum pump for vacuum impregnation again, filter and dry, bury the mixture at carbon high temperature to obtain modified graphite; The base material is made of rubber, modified talcum powder, butyl acetate, bisphenol F liquid epoxy resin, conductive material, antioxidant, modified sulfur and modified graphite, and then a foaming agent is added to produce a soft layer. The soft layer and the base layer can be connected together to enhance the impact resistance of the rubber pad, improve the impact absorption and vertical deformation capabilities, and prevent static electricity accumulation.

[0027] A production process for an antistatic rubber floor mat comprises the following steps: S1: Weigh rubber material, modified talcum powder, butyl acetate and bisphenol F liquid epoxy resin according to proportion, pour them into a rubber kneading machine, knead and pound the rubber, take out the material after 10 minutes of operation to obtain a mixed rubber, add the mixed rubber to an open mill for plastication to obtain a masterbatch; S2: The masterbatch is transferred into an internal mixer, and then antioxidant and modified graphite are added into the internal mixer, and mixed under high temperature and high shear conditions. The speed of the internal mixer is controlled at 160r / min, the cooling water temperature is controlled at 45°C, and the mixing time is controlled at 3 minutes. Then, the conductive material and modified sulfur are added, and conventional internal mixing is performed to obtain a base compound rubber; S3: Take one third of the base layer rubber mix, add a foaming agent and continue mixing to obtain a soft layer rubber mix; S4: pouring the base rubber mixture into the bottom of the mold, and then spreading the soft layer rubber mixture on the base rubber mixture, and performing compression molding at a pressure of 11 MPa for 20 minutes, and taking out the semi-finished floor mat; S5: The floor mat is glued to the semi-finished product by gluing to obtain an anti-static rubber floor mat.

[0028] Comparing the conventional rubber floor mat with the rubber floor mat prepared in Examples 1 to 5, the rubber floor mats prepared in Examples 1 to 5 are shown in the following table: Comparative Example Embodiment 1 Embodiment 2 Embodiment 3 Embodiment 4 Embodiment 5 Shock absorption (%) 37 49 50 49 48 48 Vertical deformation (mm) 1.4 1.9 2.0 1.9 1.8 1.8 Determination of effectiveness of anti-static ability Failure qualified qualified qualified qualified qualified It can be seen from the above table that the impact absorption and vertical deformation capabilities of the rubber floor mat prepared by the present invention are significantly improved, the antistatic performance is guaranteed, and implementation 2 is the best implementation example.

[0029] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. An antistatic rubber floor mat, characterized in that: The antistatic rubber floor mat comprises a base layer, a soft layer bonded to the top of the base layer, and a floor mat cloth bonded to the top of the soft layer: The raw material composition and weight proportion of the base layer include 45 to 65 parts of rubber material, 6 to 10 parts of modified talc powder, 1 to 5 parts of butyl acetate, 7 to 10 parts of bisphenol F type liquid epoxy resin, 10 to 15 parts of conductive material, 1 to 3 parts of antioxidant, 8 to 12 parts of modified sulfur and 6 to 10 parts of modified graphite; The raw material composition and weight proportion of the soft layer include 98 parts of base rubber mix and 2 parts of foaming agent; The rubber material includes one or two of natural rubber, nitrile rubber, butadiene rubber and polyisoprene rubber, and the conductive material includes carbon fiber, stainless steel fiber and metal powder.

2. The antistatic rubber floor mat according to claim 1, characterized in that: The raw materials for preparing the modified talc powder include talc powder, boron nitride, ethylhexyl phosphoric acid, organic ammonium salt and ethanol. The weight ratio of talc powder, boron nitride, ethylhexyl phosphoric acid, organic ammonium salt and ethanol in the modified talc powder is 11:3:1:1:

13.

3. The antistatic rubber floor mat according to claim 2, characterized in that: The preparation method of the modified talcum powder comprises the following steps: obtaining talcum powder, boron nitride, ethylhexyl phosphoric acid, an organic ammonium salt and ethanol in proportion, adding talcum powder into ethanol, mixing and stirring with a high-speed stirrer to prepare a slurry, then adding boron nitride, ethylhexyl phosphoric acid and the organic ammonium salt into the slurry, mixing and stirring again, heating the temperature to 60°C during the mixing process, using a pellet making machine to prepare granular pills after mixing for 15 minutes, placing the granular pills into a carbonization furnace, introducing argon gas for protection, starting the carbonization furnace for heating and carbonization, the granular pills gradually undergo high-temperature graphitization, discharging the material after cooling to room temperature, and finally crushing and screening to obtain the modified talcum powder.

4. The antistatic rubber floor mat according to claim 1, characterized in that: The weight proportions of carbon fiber, stainless steel fiber and metal powder in the conductive material are 2:2:5, the length of the carbon fiber is 1mm-2mm, the length of the stainless steel fiber is 1mm-5mm, the metal powder is one of iron powder, aluminum powder and copper powder, and the particle size of the metal powder is 0.01mm-0.10mm.

5. The antistatic rubber floor mat according to claim 1, characterized in that: The materials for preparing the modified sulfur include sulfur, shell powder, acrylic resin, silane coupling agent and water. The weight ratio of sulfur, shell powder, acrylic resin, silane coupling agent and water in the modified sulfur is 5:2:3:1:

20.

6. The antistatic rubber floor mat according to claim 5, characterized in that: The preparation method of the modified sulfur comprises the following steps: pouring shell powder into water and mixing to prepare a powder suspension, adding a silane coupling agent into the powder suspension, pouring the powder suspension into a grinding device for grinding until the particle size is 5 μm to 50 μm, then adding acrylic resin for stirring for 60 to 120 minutes, then adding sulfur, accelerating stirring for 1 hour to obtain a sulfur mixture, and finally drying and dehydrating the mixture, crushing and sieving the mixture to obtain the modified sulfur.

7. The antistatic rubber floor mat according to claim 1, characterized in that: The preparation method of the modified graphite comprises the following steps: preparing graphite, potassium permanganate, citric acid and ethanol, crushing and grading the graphite to obtain a shaped graphite material, mixing the graphite, potassium permanganate and ethanol uniformly, placing the mixture in a vacuum pump for vacuum impregnation, filtering and drying, pouring deionized water into the mixture for mixing, performing a hydrothermal reaction at a temperature of 160° C. to 200° C., obtaining a solid precursor through solid-liquid separation, adding citric acid for mixing and stirring, placing the mixture in a vacuum pump for vacuum impregnation again, filtering and drying, and subjecting the mixture to carbon high temperature to obtain the modified graphite.

8. A production process for preparing an antistatic rubber floor mat as claimed in claim 1, characterized in that: The following steps are involved: S1: Weigh rubber material, modified talcum powder, butyl acetate and bisphenol F liquid epoxy resin according to proportion, pour them into a rubber kneading machine, knead and pound the rubber, take out the material after 10 minutes of operation to obtain a mixed rubber, add the mixed rubber to an open mill for plastication to obtain a masterbatch; S2: The masterbatch is transferred into an internal mixer, and then antioxidant and modified graphite are added into the internal mixer, and mixed under high temperature and high shear conditions. The mixing time is controlled within 3 minutes, and then conductive material and modified sulfur are added, and conventional internal mixing is performed to obtain a base compound rubber; S3: Take one third of the base layer rubber mix, add a foaming agent and continue mixing to obtain a soft layer rubber mix; S4: pour the base layer rubber mixture into the bottom of the mold, then spread the soft layer rubber mixture on the base layer rubber mixture, press mold to form, and take out the semi-finished floor mat; S5: The floor mat is glued to the semi-finished product by gluing to obtain an anti-static rubber floor mat.

9. The production process of an antistatic rubber floor mat according to claim 8, characterized in that: In S2, the speed of the internal mixer is controlled at 150 r / min to 170 r / min, and the temperature of the cooling water is controlled at 40° C. to 50° C.

10. The production process of an antistatic rubber floor mat according to claim 8, characterized in that: In S4, compression molding is performed under a pressure condition of 10 MPa to 12 MPa, and the compression molding time is 20 minutes.

Citation Information

Patent Citations

  • A method for manufacturing a rubber pad and the rubber pad itself.

    CN112477139B

  • Elastic safety rubber mat and preparation method thereof

    CN104523109A

  • Anti-static rubber floor board and production method thereof

    CN105525739A

  • Coal conveyer rubber conveyer belt capable of eliminating static electricity

    CN106081482A

  • Preparation method of antistatic carbon nano nitrile butadiene rubber covered roller composite

    CN106832469A